Adherence to metformin monotherapy in people with type 2 diabetes mellitus in New Zealand. (December 2019) - Horsburgh, Simon; Barson, David; Zeng, Jiaxu; Sharples, Katrina; Parkin, Lianne
Abstract: Aim: To describe adherence to metformin monotherapy in New Zealanders with type 2 diabetes mellitus (T2DM) initiating pharmacological treatment for the first time. Methods: We created a cohort of all New Zealanders with T2DM commencing metformin monotherapy between 1 January 2006 and 30 September 2014 using national data collections and followed them until the end of 2015. We obtained data on person- and health-related characteristics at metformin initiation from these collections and calculated medication possession ratios from pharmacy dispensing data. Regression modelling was used to assess changes in adherence over time. Results: We identified 85, 066 people with T2DM who initiated metformin monotherapy. Lower adherence to metformin monotherapy was associated with time since initiating metformin, younger age and being of Māori or Pacific ethnicity. Higher adherence was associated with receiving more non-diabetic medications, a history of CVD and recent cancer registration. Conclusions: Our findings are consistent with international literature and highlight groups of people who experience poor adherence over time. Understanding the drivers of lower adherence in Māori and Pacific peoples is a particular priority given the high prevalence of T2DM in these populations.